Development of the Middle Layer in the Anther of Arabidopsis - Xue, Jing-Shi; Yao, Chi; Xu, Qin-Lin; Sui, Chang-Xu; Jia, Xin-Lei; Hu, Wen-Jing; Lv, Yong-Lin; Feng, Yi-Feng; Peng, Yu-Jia; Shen, Shi-Yi; Yang, Nai-Ying; Lou, Yu-Xia; et al. (Frontiers in Plant Science, 2021)
The middle layer is an essential cell layer of the anther wall located between the endothecium and tapetum in Arabidopsis. Based on sectioning, the middle layer was found to be degraded at stage 7, which led to the separation of the tapetum from the anther wall. Here, we established techniques for live imaging of the anther. We created a marker line with fluorescent proteins expressed in all anther layers to study anther development. Several staining methods were used in the intact anthers to study anther cell morphology. We clarified the initiation, development, and degradation of the middle layer in Arabidopsis. This layer is initiated from both the inner and outer secondary parietal cells at stage 4, stopped cell division at stage 6, and finally degraded at stage 11. The neighboring cell layers, the epidermis, and endothecium continued cell division until stage 10, which led to a thin middle layer. The degradation of the tapetum cell wall at stage 7 lead to its isolation from the anther wall. This work presents fundamental information on the development of the middle layer, which facilitates the further investigation of anther development and plant fertility. These live imaging methods could be useful in future studies.